1975
DOI: 10.1002/cncr.2820360942
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma: A clinicopathologic study and long‐term followup of 60 patients

Abstract: The clinical courses of 60 patients with hemangiopericytoma of the somatic soft tissues are summarized in this retrospective study. The tumors were subjected to a comparative histologic review and classified as benign (12 lesions), borderline malignant (16 lesions), and malignant (32 lesions). Tumors with 1 mitotic figure per 10 high‐power fields and slight cellular anaplasia or 1 mitotic figure per 20 high‐power fields and moderate cellular anaplasia may be expected to follow a malignant clinical course. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
126
0
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(131 citation statements)
references
References 29 publications
3
126
0
2
Order By: Relevance
“…Historically, hemangiopericytomas have been reported to have a worse prognosis than solitary fibrous tumor, with 5-and 10-year hemangiopericytoma survival rates as low as 59 and 47-70%, respectively, 3,15 and up to 48% disease-specific mortality. 16 In pleural solitary fibrous tumor, recurrence and mortality are reportedly predicted by both histology and resectability; typically, benign pedunculated tumors excised with clear margins have a recurrence rate of 2%, while sessile malignant solitary fibrous tumors may recur up to 63% of the time, resulting in a 30% mortality rate. 8,17 Extrathoracic solitary fibrous tumors behave similarly; diseasespecific death accounted for only 3 patients in one series of 75 patients 10 and no patients in a series of 24 cases with up to 20-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, hemangiopericytomas have been reported to have a worse prognosis than solitary fibrous tumor, with 5-and 10-year hemangiopericytoma survival rates as low as 59 and 47-70%, respectively, 3,15 and up to 48% disease-specific mortality. 16 In pleural solitary fibrous tumor, recurrence and mortality are reportedly predicted by both histology and resectability; typically, benign pedunculated tumors excised with clear margins have a recurrence rate of 2%, while sessile malignant solitary fibrous tumors may recur up to 63% of the time, resulting in a 30% mortality rate. 8,17 Extrathoracic solitary fibrous tumors behave similarly; diseasespecific death accounted for only 3 patients in one series of 75 patients 10 and no patients in a series of 24 cases with up to 20-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, older series also found higher metastatic rates in hemangiopericytoma and pleural solitary fibrous tumor-from 18 to 50%. 2,3,16,20 This variability may be due in part to differences in follow-up time as well as referral bias. Adequate follow-up time is required to determine metastatic frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies of conventional HPC, conducted before the routine use of immunohistochemical techniques to identify cell types of soft tissue sarcomas, are revealing. In an evaluation of 60 patients, McMaster et al 18 found that 48% had died of disease. Of the19 patients reported by Auguste et al, 19 53% developed pulmonary metastases; the overall survivals were 59% and 47% at 5 and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%